Estudios para la configuracioń de las facies cerámicas altoimperiales en el Sur de la Península Ibérica - Ruiz Montes, Pablo; Ruiz Montes, Pablo; Peinado Espinosa, María Victoria; Peinado Espinosa, María Victoria; Fernández García, María Isabel; Fernández García, María Isabel (Roman and late antique Mediterranean pottery, 2018)
An exploration of the economy and trade in the South of the Iberian Peninsula during the High Roman Empire, focusing on the study of ceramic contexts in several market places and consumption centres located in the region